Underlying Thermodynamics of pH-Dependent Allostery - Di Russo, Natali V. (2014)
Understanding the effects of coupling protein protonation and conformational states is critical to the development of drugs targeting pH sensors and to the rational engineering of pH switches. In this work, we address this issue by performing a comprehensive study of the pH-regulated switch from the closed to the open conformation in nitrophorin 4 (NP4) that determines its pH-dependent activity. Our calculations show that D30 is the only amino acid that has two significantly different pKas in the open and closed conformations, confirming its critical role in regulating pH-dependent behavior. In addition, we describe the free-energy landscape of the conformational change as a function of pH, obtaining accurate estimations of free-energy barriers and equilibrium constants using different methods. The underlying thermodynamic model of the switch workings suggests the possibility of tuning the observed pKa only through the conformational equilibria, keeping the same conformation-specific pKas, as evidenced by the proposed K125L mutant. Moreover, coupling between the protonation and conformational equilibria results in efficient regulation and pH-sensing around physiological pH values only for some combinations of protonation and conformational equilibrium constants, placing constraints on their possible values and leaving a narrow space for protein molecular evolution. The calculations and analysis presented here are of general applicability and provide a guide as to how more complex systems can be studied, offering insight into how pH-regulated allostery works of great value for designing drugs that target pH sensors and for rational engineering of pH switches beyond the common histidine trigger.